Correlation between T2 (T2 star) relaxation time and cervical intervertebral disc degeneration: An observational study - Huang, Minghua; Guo, Yong; Ye, Qiong; Chen, Lei; Zhou, Kai; Wang, Qingjun; Shao, Lixin; Shi, Qinglei; Chen, Chun (Medicine (Baltimore), 2016)
To demonstrate the potential benefits of T2 relaxation time of intervertebral discs (IVDs) regarding the detection and grading of degenerative disc disease using 3.0-T magnetic resonance imaging (MRI) in a clinical setting. Cervical sagittal T2-weighted, T2 relaxation MRI was performed at 3.0-T in 61 subjects, covering discs C2-3 to C6-7. All discs were morphologically assessed based on the Pfirrmann grade, and regions of interests (ROIs) were drawn over the T2 mapping. Receiver operating characteristic (ROC) analysis was performed among grades to determine the cut-off values. Cervical intervertebral discs (IVDs) of patients were commonly determined to be at Pfirrmann grades III to V. The nucleus pulposus (NP) values did not differ significantly between sexes at the same anatomic level (P > 0.05). In the NP, the T2 values tended to decrease with increasing grade (P < 0.000), and a significant difference was found in the T2 values between grades I to V (P < 0.05). T2 values based on disc degeneration level classification were as follows: grade I (>30 milliseconds), grade II (24.55-29.99 milliseconds), grade III (21.65-24.54 milliseconds), grade IV (18.35-21.64 milliseconds), and grade V (<18.34 milliseconds). Our standardized method of region-specific quantitative T2 relaxation time evaluation seems capable of characterizing different degrees of disc degeneration quantitatively. The T2 values obtained in these cervical IVDs may serve as baseline values for future T2 measurements in both healthy and degenerated cervical discs.